A carbazole-functionalized metal–organic framework for efficient detection of antibiotics, pesticides and nitroaromatic compounds. Issue 8 (1st February 2019) - Xu, Ning; Zhang, Qinghua; Zhang, Guoan
Abstract : A carbazole-functionalized Cd-MOF exhibits highly selective and sensitive fluorescence detection towards antibiotics, pesticides and nitroaromatic compounds. Abstract : Organic pollutants, such as antibiotics, pesticides, and nitroaromatic compounds (NACs), have posed a great threat to human health and sustainable development. Therefore, the detection of these organic pollutants is of great importance but challenging. In this work, we synthesized a rigid conjugated tricarboxylic acid ligand 4, 4′-(9-(4′-carboxy-[1, 1′-biphenyl]-4-yl)-9 H -carbazole-3, 6-diyl)dibenzoic acid (H3 CBCD), and employed this ligand to react with Cd(ii ) ions to construct a Cd-LMOF, namely [Cd3 (CBCD)2 (DMA)4 (H2 O)2 ]·10DMA (Cd-CBCD). Cd-CBCD features a three-dimensional (3D) supramolecular framework based on two-dimensional (2D) layer structures through π⋯π stacking interactions. The fluorescence sensing measurements demonstrate that Cd-CBCD can detect nitrofurans (NFs), 4-nitroaniline (4-NA) and 2, 6-dichloro-4-nitroaniline (DCN) with high selectivity and sensitivity. This work represents the first carbazole-functionalized metal–organic framework as a fluorescent sensor for the highly efficient detection of antibiotics, pesticides and nitroaromatic compounds.